2019
DOI: 10.3390/biomedicines7010019
|View full text |Cite
|
Sign up to set email alerts
|

Current Knowledge of IL-6 Cytokine Family Members in Acute and Chronic Kidney Disease

Abstract: Healthy kidneys are important for the efficient regulation of metabolism. However, there is an ever increasing population of patients suffering from both acute and chronic kidney diseases that disrupt this homeostasis. This review will explore the emerging roles that interleukin 6 (IL-6) cytokine family members play in the pathogenesis of kidney disease. The IL-6 family of cytokines are involved in a diverse range of physiological functions. In relation to kidney disease, their involvement is no less diverse. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 96 publications
(131 reference statements)
0
22
0
Order By: Relevance
“…IL-6 is an important cytokine in the progression of CKD. In previous studies, increased levels of IL-6 were found in renal tissues of CKD patients and were related to risk of CKD complications [51,52]. Honda et al demonstrated that IL-6 was a reliable predictor of CKD related malnutrition and cardiovascular diseases [53].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…IL-6 is an important cytokine in the progression of CKD. In previous studies, increased levels of IL-6 were found in renal tissues of CKD patients and were related to risk of CKD complications [51,52]. Honda et al demonstrated that IL-6 was a reliable predictor of CKD related malnutrition and cardiovascular diseases [53].…”
Section: Discussionmentioning
confidence: 98%
“…Kamińska et al suggested that the serum level of IL-6 was associated with coronary artery calcification and 5-year risk of all-cause mortality in CKD patients 54 , 55 . Importantly, renal cells, including podocytes, mesangial cells, endothelial cells and so forth , may express and secrete IL-6 51 . In kidney, IL-6 could act as both a proinflammatory and an anti-inflammatory factor to promote cell proliferation, differentiation and tubulointerstitial fibrosis 56 .…”
Section: Discussionmentioning
confidence: 99%
“…In our data set, aldosterone sustainably repressed three interleukins transcripts, CXCL8 plus IL-6 and IL11 belonging to the IL-6 cytokine family, and the chemokine CCL7. Elevated expression of CXCL8 and IL-6 were previously shown to be detrimental in diabetic nephropathy in mouse and human [33][34][35][36][37] and, together with IL11, in acute kidney injury (AKI). 38 The interleukins and CCL7 are also involved in kidney fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, podocyte is the only renal cell expressing IL-6R [36]. IL-6 induces signal transducers and activators of transcription (STAT), mitogen-activated protein kinase (MAPK) and phosphoinositide 3-kinase (PI3K) [37], italso potentiates effects of angiotensin II on the kidneys [34]. In the experiment with IL-6 knockout mice, IL-6 was the key regulator for exacerbation of albuminuria and renal fibrosis [38].…”
Section: Discussionmentioning
confidence: 99%